The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1002/ecs2.1663
|View full text |Cite
|
Sign up to set email alerts
|

Restoring surface fire stabilizes forest carbon under extreme fire weather in the Sierra Nevada

Abstract: Abstract. Climate change in the western United States has increased the frequency of extreme fire weather events and is projected to increase the area burned by wildfire in the coming decades. This changing fire regime, coupled with increased high-severity fire risk from a legacy of fire exclusion, could destabilize forest carbon (C), decrease net ecosystem exchange (NEE), and consequently reduce the ability of forests to regulate climate through C sequestration. While management options for minimizing the ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 63 publications
3
52
0
Order By: Relevance
“…Although reducing wildfire emissions requires repeated atmospheric C emissions from more frequent prescribed fires (Hurteau ; Krofcheck et al . ), prescribed fire emissions are smaller and we found support for our hypothesis that large‐scale treatments will lower fire severity and reduce wildfire emissions relative to the control (Figures and ). Inclusive of emissions from repeated prescribed fire, our large‐scale restoration treatments reduced fire emissions by an average of 0.07–0.09 Mg C ha −1 yr −1 over the 90‐year simulation, with the cumulative amount of avoided C emissions across the entire Sierra Nevada equaling 24% of California's 2020 emission limit (116 Tg; California Assembly Bill 32).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Although reducing wildfire emissions requires repeated atmospheric C emissions from more frequent prescribed fires (Hurteau ; Krofcheck et al . ), prescribed fire emissions are smaller and we found support for our hypothesis that large‐scale treatments will lower fire severity and reduce wildfire emissions relative to the control (Figures and ). Inclusive of emissions from repeated prescribed fire, our large‐scale restoration treatments reduced fire emissions by an average of 0.07–0.09 Mg C ha −1 yr −1 over the 90‐year simulation, with the cumulative amount of avoided C emissions across the entire Sierra Nevada equaling 24% of California's 2020 emission limit (116 Tg; California Assembly Bill 32).…”
Section: Discussionsupporting
confidence: 79%
“…; Krofcheck et al . ). The temporal distribution of C losses demonstrated that large‐scale restoration treatments may initially incur greater C loss from the system, with the size of this near‐term C cost being a function of implementation timing (Figure ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…❖ www.esajournals.org 4 November 2019 ❖ Volume 10(11) ❖ Article e02934 forest succession and interactions with fire, harvest, wind, and insects (Scheller et al 2008, Duveneck et al 2014, Kretchun et al 2016, Krofcheck et al 2017, Lucash et al 2017. LANDIS-II uses the life-history traits of tree and shrub species, along with soil and climate data, to simulate succession and responses to disturbances over time.…”
Section: Overview Of Simulation Modelmentioning
confidence: 99%
“…The NECN extension implements succession with above-and belowground carbon and nitrogen and simulates the regeneration and growth of vegetation based on age, competition for resources (water, nitrogen, light), and disturbance. Prescribed fires are, however, only currently being simulated within the Biomass Harvest extension , Hurteau 2017, Krofcheck et al 2017, Swanteson-Franz et al 2018. Dead biomass (woody and leaf litter) and soil organic carbon (SOC) are also tracked over time.…”
Section: Simulation Modeling Frameworkmentioning
confidence: 99%